Turbulent plane Couette flow at moderately high Reynolds number. (25th July 2014) - Avsarkisov, V.; Hoyas, S.; Oberlack, M.; García-Galache, J. P.
Abstract A new set of numerical simulations of turbulent plane Couette flow in a large box of dimension (<alternatives><inline-graphic xlink:href="ark:/27927/pghw30f69s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\def \xmlpi #1{}\def \mathsfbi #1{\boldsymbol {\mathsf {#1}}}\let \le =\leqslant \let \leq =\leqslant \let \ge =\geqslant \let \geq =\geqslant \def \Pr {\mathit {Pr}}\def \Fr {\mathit {Fr}}\def \Rey {\mathit {Re}}20\pi h, \, 2h, \, 6\pi h$]]> </alternatives>) at Reynolds number <alternatives><inline-graphic xlink:href="ark:/27927/pghw30f67r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$(\mathit{Re}_{\tau }) =125$]]> </alternatives>, 180, 250 and 550 is described and compared with simulations at lower Reynolds numbers, Poiseuille flows and experiments. The simulations present a logarithmic near-wall layer and are used to verify and revise previously known results. It is confirmed that the fluctuation intensities in the streamwise and spanwise directions do not scale well in wall units. The scaling failure occurs both near to and away from the wall. On the contrary, the wall-normal intensity scales in inner units in the near-wall region and in outer units in the core region. The spectral ridge found by Hoyas & Jiménez (Phys. Fluids, vol. 18, 2003, 011702) for the turbulent Poiseuille flow can also be seen in the present flow. Away from the wall, very large-scale motions are found spanning through all the length of the channel. The statistics of these simulations can be downloaded from the webpage of the Chair of Fluid Dynamics.